Malignant Peritoneal Mesothelioma: Report of a Rare and Challenging Surgical Case - Okomayin, A. A.; Dongo, A. E.; Azeke, T.; Tagar, E.; Odion, C.; Okoeguale, J.; Ozah, E.; Eluehike, S.; Lar, D. (International Journal For Research In Health Sciences And Nursing, 2021)
Malignant peritoneal mesothelioma is a rare tumour of mesothelial origin arising from the peritoneal linings and its incidence is second to pleural mesothelioma. Clinical presentation is often vague and non-specific posing great difficulty and delay in diagnosis. Thankfully, the biological behaviour and spread of the tumour makes local treatment with combine cytoreductive surgery and chemotherapy the standard first line treatment. We report a challenging case in a 50 year-old woman who presented with symptoms of 9 months duration and had cytoreductive surgery and adjuvant chemotherapy following histological confirmation of malignant peritoneal mesothelioma.